1993
DOI: 10.1203/00006450-199306000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Treatment for Acute Lymphoblastic Leukemia with and without Cranial Irradiation on Growth and Puberty: A Comparative Study

Abstract: ABSTRACT. We investigated the comparative effect on long-term growth of CNS prophylactic treatment for acute lymphoblastic leukemia (ALL) with either 25-Gy cranial irradiation or moderate-dose i.v. methotrexate. In 80 children with complete continuous first remission, data on growth and pubertal development were investigated up to 11 y from ALL diagnosis. Forty patients had 25-Gy cranial irradiation, 16 of them with high-risk factors and 24 without. Another 40 non-high-risk ALL patients had moderate-dose metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
30
1
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 16 publications
9
30
1
5
Order By: Relevance
“…Contrary to some (2,3,10,11,15,18) but not all previous studies (6,14), we found that compared with siblings, patients treated with chemotherapy alone had mildly shorter mean adult heights and a three-fold increased risk of short adult stature across age groups, pubertal status, and secular time periods, even after adjustment for possible demographic confounding variables. Differences in results between this study and others may stem from differences in the definition of "adult/final" heights and in comparison groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to some (2,3,10,11,15,18) but not all previous studies (6,14), we found that compared with siblings, patients treated with chemotherapy alone had mildly shorter mean adult heights and a three-fold increased risk of short adult stature across age groups, pubertal status, and secular time periods, even after adjustment for possible demographic confounding variables. Differences in results between this study and others may stem from differences in the definition of "adult/final" heights and in comparison groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect on loss of stature was greater in children who also received radiotherapy to the spine, secondary to direct inhibition of vertebral growth(13). For most studies in which the impact of chemotherapy without radiotherapy was examined, growth suppression during treatment was followed by catch-up growth (2,3,10,11,15,18). However, catch-up growth has not been observed consistently across studies(6,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged survival of children with acute lymphoblastic leukemia (ALL) has changed the focus to the various late effects of the disease and its treatment. Possible serious late effects of ALL and its treatment are second cancers, cardiac dysfunction, renal damage, pulmonary toxicity, hearing loss, dental changes, obesity, hypogonadism, growth retardation, and decreased bone mass [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of poor growth in children with acute lymphoblastic leukemia (ALL), especially during periods of intensive chemotherapy, but growth may return to normal during less-intensive periods and may show evidence of further catch-up after completion of chemotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Of greater concern are a number of retrospective crosssectional studies on survivors of ALL that describe reduced bone mineral density (BMD) at various sites (14 -16).…”
mentioning
confidence: 99%